Business Feasibility of Intensive Vaname Shrimp (Litopenaeus vannamei) with Non-Partial System - Wafi, Abdul; Ariadi, Heri; Muqsith, Abdul; Madusari, Benny Diah (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2021)
Shrimp farming with a non-partial harvest system is a cultivation concept to obtain optimal production harvest. The purpose of this study was to determine the business feasibility status of vaname shrimp (L. vannamei) cultivation with a non-partial harvesting system in terms of the ecological and financial aspects from aquaculture. The research method used in this study is a survey research method with data collection techniques based on purposive sampling. The results showed, this non-partial system is ecologically very feasible, because the conditions of the average daily water quality parameter values (DO, pH, temperature, salinity) during the aquaculture period are still above the water quality standard threshold for intensive aquaculture. The business financial feasibility analysis resulted in a profit of IDR 441,307,102,-, BEP Unit 2,062 Kg, BEP Sales IDR 119,995,253,-, R/C of 1.71, Return on Investment of 47.69%, and Payback Period of 2.7 years. Meanwhile based on investment analysis, the Net Present Value of IDR 34,136,139,245,-, Net B/C 11.61, and Internal Rate of Return 37.23%. So, it can be denied, that based on ecological aspects and economic multiplication of aquaculture systems like this can be categorized as very feasible and profitable to be globally developed.